Analysis of Different Call Service Influence for Telecommunication Network Performance - Gedmantas, R.; Jarutis, A. (Elektronika ir Elektrotechnika, 2005)
Analysis of intelligent services deployment influence on the telecommunications network is presented. Supplementary services are provided in existing networks introducing intellect into switching systems and using additional nodes. Indication that deployment of intelligent services imposes additional load on the network nodes is given in this work. Analytical model of IN comprised of SSP and SCP nodes is created using Markov chain theory. Analysis of dependence of the IN performance characteristics on the ratio of intelligent and simple service requests with constant summary request rate is presented herein. Intelligent services deployment influence on existing network must be estimated before deployment in actual PSTNs. This work proposes that either request service capacity of existing service nodes must be increased or additional service processors deployed in accordance with estimated changes in the traffic. Ill. 6, bibl. 4 (in Lithuanian; summaries in Lithuanian, English, Russian).